On the destruction of Yugoslavia - Mrkić, Ivan (Napredak, 2021)
In this paper we discuss the development of the SFRY, especially in the period before and after the passing of its Constitution in February 1974. We comment on the behavior of the Serbian representatives during that time. We pay special attention to the term “dissolution”, which we explain and deem unfounded, as many events point to the conclusion that Yugoslavia, a signatory of the UN Charter, was broken up and destroyed both politically and physically. We explain who the subjects were who believed that the benefits of destroying Yugoslavia should fall on secessionist politics. We discuss the role of the European Community and the western world, looking back at the so-called Carrington Conference. The paper also mentions the names and roles of certain Yugoslav and foreign political figures. The role of Germany is also discussed.
Keywords: responsibility of the leadership of the SFRY; Carrington Conference; London Conference; role of the West and the European Community